The Role of Corticosteroids in the Management of Drug Allergy: A Narrative Literature Review - Rivani Sintia Suratman; Rudy Afriant; Roza Mulyana; Saptino Miro; Deka Viotra (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2023)
Drug allergy is an adverse drug reaction that occurs through an immune reaction that occurs through IgE or a rapid hypersensitivity reaction with various mechanisms and clinical presentations. One of the therapeutic modalities for drug allergies is corticosteroids. In allergic processes, corticosteroids can suppress the production and effects of humoral factors involved in the inflammatory response, inhibit the migration of leukocytes to sites of inflammation, and interfere with the function of endothelial cells, granulocytes, mast cells, and fibroblasts. This literature review aimed to describe the role of corticosteroids in the management of drug allergies. Corticosteroids are used very widely in the treatment of various allergic diseases because of their strong anti-inflammatory properties. Corticosteroids inhibit the synthesis of a number of cytokines, such as the interleukins IL-1 to IL-6, tumor necrosis factor-α (TNF-α), and granulocyte-macrophage colony-stimulating factor (GM-CSF). In conclusion, corticosteroids are one of the therapeutic modalities in various manifestations of drug allergies. Every drug allergy gets the anti-inflammatory effects of corticosteroids with different choices, routes, and doses for each manifestation.